Knowledge, Attitude and Practice of Infection Control Among Dental Students at College of Dentistry - Hawler Medical University. - Abduljaleel Azad Samad; Jodal M. Ahmed; Karin Zaki Izzat; Saya Saman Abdulqadir; Marwa Qadir Muhammed; Muzhda Ayub Bakir (Erbil Dental Journal)
Background: Infections acquired in healthcare facilities have become an increasingly challenging issue worldwide. The prevention of infectious diseases is a critical issue since healthcare workers develop acquired infections while providing services to patients. However, infection prevention and control are challenging, especially in healthcare facilities.